The predictive potential of peripheral blood basophils in endometriosis - Guan, J; Hellner, K; Rahmioglu, N; Hubbard, C; Dale, M; Paddon, K; Zondervan, K; Becker, C (SAGE Publications, 2017)
Endometriosis affects 5-10% of premenopausal women causing pelvic pain and impaired fertility. Diagnosis can only be established surgically, thus, less invasive means of diagnosis are urgently needed. Endometriosis has been suggested to induce local and systemic inflammation. Circulating leukocytes are used as markers of systemic inflammatory response in many conditions. However, their role in endometriosis is unclear. This study investigates the potential of leukocyte subpopulations in diagnosing endometriosis, using data from prospective ENDOX study.